2011
DOI: 10.1111/j.1399-3054.2011.01530.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide as a critical factor for perception of UV‐B irradiation by microtubules in Arabidopsis

Abstract: Influence of ultraviolet-B (UV-B) as an abiotic stress factor on plant microtubules (MTs) and involvement of nitric oxide (NO) as a secondary messenger mediating plant cell response to environmental stimuli were investigated in this study. Taking into account that endogenous NO content in plant cells has been shown to be increased under a broad range of abiotic stress factors, the effects of UV-B irradiation and also the combined action of UV-B and NO donor sodium nitroprusside (SNP) or NO scavenger 2-(4-carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
3

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 45 publications
(78 reference statements)
0
37
0
Order By: Relevance
“…The structure and dynamics of cytoskeleton, the main cellular players in stomatal movement (Huang et al, 2009;Eisinger et al, 2012aEisinger et al, , 2012b) that can control ion channels in guard cells (Zhang et al, 2007), have been shown to be regulated by NO as well as H 2 O 2 (Huang et al, 2009;Wilkins et al, 2011;Yemets et al, 2011). Recent evidence also suggests that NO mediates UV-B signaling in plant cells by modulating cytoskeleton (Yemets et al, 2011;Krasylenko et al, 2012). Thus, whether the UV-B-dependent NO induces stomatal closure via modulating cytoskeleton and the subsequent activation of ion channels is an interesting question to be addressed in the future.…”
Section: Nia1-dependent No Mediates Uv-b-induced Stomatal Closurementioning
confidence: 99%
“…The structure and dynamics of cytoskeleton, the main cellular players in stomatal movement (Huang et al, 2009;Eisinger et al, 2012aEisinger et al, , 2012b) that can control ion channels in guard cells (Zhang et al, 2007), have been shown to be regulated by NO as well as H 2 O 2 (Huang et al, 2009;Wilkins et al, 2011;Yemets et al, 2011). Recent evidence also suggests that NO mediates UV-B signaling in plant cells by modulating cytoskeleton (Yemets et al, 2011;Krasylenko et al, 2012). Thus, whether the UV-B-dependent NO induces stomatal closure via modulating cytoskeleton and the subsequent activation of ion channels is an interesting question to be addressed in the future.…”
Section: Nia1-dependent No Mediates Uv-b-induced Stomatal Closurementioning
confidence: 99%
“…[21][22][23][24][25] It was shown recently that the interphase and mitotic MTs in epidermal and cortex cells of all primary root zones of Arabidopsis thaliana L. seedlings expressing gfp-map4 (microtubule-assosiated protein 4) were randomized, depolymerized and/or stabilized in dose-dependent manner after the UV-B exposure (13.6-68 kJ/m 2 ) in vivo that was accompanied by the cell swelling and excessive root hairs formation. 26 Our further experiments give additional evidences that plant MTs are involved in signal transduction under UV-B stress. The experimental system based on A. thaliana (GFP-MAP4) 4 d-old seedlings having their primary roots protected with aluminum foil downwards from the hypocotyls (hereinafter referred to as shielded seedlings) to avoid the direct UV-B exposure were designed.…”
mentioning
confidence: 53%
“…32 We have shown also that immediately after the UV-B exposure (13.6-68 kJ/m 2 ) cortical MTs in both transition and elongation zones depolymerized rapidly. 26 Furthermore, UV-B-induced MTs reorganization in root cells of shielded A. thaliana seedlings was accompanied by primary root growth inhibition (Fig. 1II, 27.2 kJ/m 2 UV-B, shielded roots, 68 kJ/m 2 UV-B, shielded roots, respectively) and epidermal cells swelling together with the intense root hairs formation in differentiation zone (Fig.…”
Section: Acknowledgmentsmentioning
confidence: 94%
“…It was also indicated that NO is involved in secondary metabolite production. Recently, it was suggested that UV-B-enhanced NO levels in plant cells can also protect microtubule organization as well as microtubule-related processes of root growth and development against disrupting effects of UV-B (Krasylenko et al 2012). …”
Section: Uv-b Radiationmentioning
confidence: 99%